A randomized, placebo-controlled, double-blind phase IIb trial evaluating the safety and efficacy of tirasemtiv in patients with amyotrophic lateral sclerosis. Issue 5 (17th August 2016) - Shefner, Jeremy M.; Wolff, Andrew A.; Meng, Lisa; Bian, Amy; Lee, Jacqueline; Barragan, Donna; Andrews, Jinsy A.; ,
Abstract: Our objectives were to evaluate the safety and tolerability of tirasemtiv over 12 weeks and its effect on the revised ALS Functional Rating Scale (ALSFRS-R) and other secondary functional measures. This randomized, double-blind, placebo-controlled trial enrolled adults with ALS and slow vital capacity (SVC) > 50% from 73 centers in eight countries. Patients who tolerated open-label tirasemtiv 125 mg b.i.d. for one week were randomized to double-blind treatment either to placebo or tirasemtiv, escalating to a maximum tolerated dose up to 250 mg b.i.d. The primary endpoint was the change from baseline in ALSFRS-R; secondary endpoints included SVC, maximum voluntary ventilation, sniff nasal inspiratory pressure, isometric muscle strength, and sub-maximum handgrip fatigue. Of 711 patients enrolled, 596 were randomized and received at least one dose of double-blind treatment. The primary endpoint showed no treatment effect (tirasemtiv: −2.98 ± 0.28, placebo: −2.40 ± 0.25, p = 0.114); however, SVC and muscle strength declined significantly more slowly on tirasemtiv (95% CI p = 0.0006, p = 0.0158, respectively). Dropouts and serious adverse events occurred more frequently in the tirasemtiv group. In conclusion, this was a negative study with respect to the primary endpoint; however, the effects on SVC and muscle strength suggest a potentially important effect of tirasemtiv warranting further evaluation over a longer period in ALS.